Antidepressant Drugs and Physical Activity: A Possible Synergism in the Treatment of Major Depression? - Guerrera, Claudia Savia; Furneri, Giovanna; Grasso, Margherita; Caruso, Giuseppe; Castellano, Sabrina; Drago, Filippo; Di Nuovo, Santo; Caraci, Filippo (Frontiers in Psychology, 2020)
Major depressive disorder (MDD) is a severe mental illness that affects 5 to 20% of the general population. Current antidepressant drugs exerts only a partial clinical efficacy because approximately 30% of depressed patients failed to respond to these drugs and antidepressants produce remission only in 30% of patients. This can be explained by the fact that the complex pathophysiology of depression has not been completely elucidated, and treatments have been mainly developed following the “monoaminergic hypothesis” of depression without considering the key role of other factors involved in the pathogenesis of MDD, such as the role of chronic stress and neuroinflammation. Chronic stress acts as a risk factor for the development of MDD through the impairment of neurotrophins signaling such as brain-derived neurotrophic factor (BDNF) and transforming-growth-factor-β1 (TGF-β1). Stress-induced depressive pathology contributes to altered BDNF level and function in MDD patients and, thereby, an impairment of neuroplasticity at the regional and circuit level. Recent studies demonstrate that aerobic exercise strongly increases BDNF production and it may contribute as a non-pharmacological strategy to improve the treatment of cognitive and affective symptoms in MDD. Here we will provide a general overview on the possible synergism between physical activity and antidepressants in MDD. Physical activity can synergize with antidepressant treatment by rescuing neurotrophin signaling in MDD patients, promoting neuronal health and recovery of function in MDD-related circuits, finally enhancing pharmacotherapeutic response. This synergism might be particularly relevant in elderly patients with late-life depression, a clinical subgroup with an increased risk to develop dementia.